When the last bus leaves: Digital citizen discourse and urban transit service failures in Surabaya - Esa Wahyu Endarti; M. Roehman Zainur Riedho; Ridha Amaliyah; Salismi Zulfi Maulidita (Faculty of Social and Political Sciences, Universitas Diponegoro, 2026)
Urban transit disruptions increasingly trigger citizen complaints on social media, yet multilingual and platform-specific discourse in the Global South remains difficult to analyze computationally. This study examines Instagram-based grievances following Surabaya transit service disruptions during the 2025-2026 New Year period. Using computational discourse analysis within a critical discourse orientation, the study analyzed 134 public comments from a government operator account and an independent civic forum through sentiment classification, thematic clustering, and multivariate modeling. Results show that negative sentiment concentrated around limited operating hours, unreliable service, weak institutional communication, and perceived governance accountability deficits. Thematic content explained sentiment variation with an exploratory pseudo-R² of 0.42, although fair human-model agreement (Cohen's κ = 0.36) and small sample size require cautious, hypothesis-generating interpretation. The findings indicate that the disruption exposed structural problems in temporal accessibility, operational reliability, information provision, and leadership accountability. The study proposes